Unconventional monetary policy and the anchoring of inflation expectations - Matteo Ciccarelli; Juan Angel García; Carlos Montes-Galdón (European Central Bank (ECB), 2017)
The effects of the unconventional monetary policy (UMP) measures undertaken by the U.S. Federal Reserve (and other major central banks) remain a crucial topic for research. This paper investigates their effects on the anchoring of long-term inflation expectations, a key dimension of UMP that has been largely overlooked. Our analysis provides two key insights. First, the anchoring of inflation expectations deteriorated significantly since late 2008. Second, the expansion of the Fed's balance sheet contributed decisively to prevent and gradually reverse that de-anchoring during the Great Recession. Using a SVAR framework extended to incorporate policy news, we show that accounting for the predictable path of the balance sheet following the Fed's asset purchase announcements is fundamental to properly assess the effects of UMP.
Keywords: E43; E44; C52; C55; 330; inflation expectations; news shocks; unconventional monetary policy